“Quando o Lateral se Torna Central” – Caso Clínico - Roriz, N; Antunes, F (Sociedade Portuguesa de Medicina Física e Reabilitação, 2012)
Pain control in rheumatological disorders is a true clinical challenge because of its multiple presentations. Unsuccessful pain control attempts, add extra difficulty to its management. Osteoarticular chronic symptoms, especially in an advanced phase, are strongly incapacitating but often undervalued despite its functional impact in patient’s life quality. Treatment options are frequently limited by its side effects, being these one of the major problems when handling different pharmacological groups. We report the case of a patient with an enteropathic arthropathy presenting with difficult persisting pain control. It reflects the importance of a correct and rigorous clinical evaluation leading to therapeutic success.
“From Side Effect to Major Concern” – Case Report
Keywords: Analgésicos; Artralgia; Doença Inflamatória Intestinal; Espondiloartropatias